The Practice of Local Bossism - Rukma, Yohanes Ivan Rukma (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
This study examines the relationship between politics and business through the case of Agus, a tobacco middleman in Bukit Hijau regency. Agus plays a pivotal role as a local boss, maintaining his position as a member of the District Regional House of Representatives (Dewan Perwakilan Rakyat Daerah tingkat Kabupaten) in the regency. Employing a qualitative research design with a phenomenological approach, data were collected through in-depth interviews. The study finds that Agus’s crucial position in the local tobacco trade system enabled his transformation into a local boss, or a local political figure, through two mobilisation channels: (1) the tobacco trade network, which he successfully converted into an electoral political network, and (2) religious networks, evidenced by his affiliation with the Nusantara Social Party (Partai Sosial Nusantara/PSN). These forms of mobilisation are analysed through six strategic frameworks for local bossism. The limitation of local bosses arises from the fact that the influence of local bosses is constrained by political party structures. The institutional system of political parties limit the full consolidation of power within the party. In conclusion, while local bosses such as Agus successfully mobilised political support through local boss strategies, their power remains incomplete and subject to institutional limitations.